Soil and seed both influence bacterial diversity in the microbiome of the Cannabis sativa seedling endosphere - Dumigan, Christopher R.; Deyholos, Michael K. (Frontiers in Plant Science, 2024)
Phytobiomes have a significant impact on plant health. The microbiome of Cannabis sativa is particularly interesting both because of renewed interest in this crop and because it is commercially propagated in two different ways (i.e. clonally and by seed). Angiosperms obtain a founding population of seed-borne endophytes from their seed-bearing parent. This study examines the influence of both seed and soil-derived bacteria on the endospheres of cannabis seedlings. A multifactorial metagenomic study was conducted with three cannabis genotypes and two soil sources, which were tested both before and after autoclave sterilization. Soil was found to have a profound effect on the alpha-diversity, beta-diversity, relative abundance, and functional genes of endophytic bacteria in germinating cannabis seedlings. Additionally, there was a significant effect of cannabis genotype on beta-diversity, especially when genotypes were grown in sterilized soil. Gammaproteobacteria and Bacilli were the two most abundant taxa and were found in all genotypes and soil types, including sterilized soil, suggesting an conserved element of cannabis seedling endosphere microbiomes is seed-derived and maintained across environments. Functional prediction of seedling endophytes using piCRUST suggested a number of important functions of seed-borne endophytes in cannabis including nutrient and amino acid cycling, hormone regulation, and as precursors to antibiotics. This study suggests both seed and soil play a critical role in shaping the microbiome of germinating cannabis seedlings.